2019
DOI: 10.1111/apa.14873
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A levels are comparable between children with newly diagnosed coeliac disease and non‐coeliac controls

Abstract: Aim: Nutritional deficiencies associated with coeliac disease include iron, folic acid and fat-soluble vitamins. This study compared the prevalence and degree of vitamin A deficiency among newly diagnosed coeliac disease patients to controls in a developed country. Methods: This prospective cohort study included all children evaluated by gastroscopy atDana-Dwek Children's Hospital, Israel, between September 2014 and February 2017. Vitamin A, haemoglobin, C-reactive protein (CRP), ferritin, tissue transglutamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…According to their results, 7.5% of patients had a deficiency of vitamin A [10]. Weintraub et al, in a study on active children with CD, did not observe an association between CD and vitamin A deficiency [32]. It should be noted that the lower quantity of fish consumed by our participating adults with active CD may have had a negative effect on their vitamin A levels.…”
Section: Discussionmentioning
confidence: 48%
“…According to their results, 7.5% of patients had a deficiency of vitamin A [10]. Weintraub et al, in a study on active children with CD, did not observe an association between CD and vitamin A deficiency [32]. It should be noted that the lower quantity of fish consumed by our participating adults with active CD may have had a negative effect on their vitamin A levels.…”
Section: Discussionmentioning
confidence: 48%
“…According to their results, 7.5% of patients revealed deficiency of vitamin A [36]. Weintraub et al in a study on active children with CD, did not observe an association between CD and vitamin A deficiency [40]. It should be noted that lower consumption of fish by our participated adults with active CD may had a negative effect on their vitamin A levels.…”
Section: Discussionmentioning
confidence: 50%
“…Most studies analyzed 25(OH)D by chemiluminescent immunoassay. Nineteen articles compared 25(OH)D levels between CD patients and control groups [8, 14, 17-20, 22, 25-28, 30-33, 35, 36, 42, 43] , of which eleven found lower 25(OH)D levels in CD patients compared with controls [17,18,20,25,28,31,33,35,36,42,43] . Eleven articles reported the numbers of patients and controls with VitD de ciency [8,14,18,22,25,26,28,30,33,35,43] , and eight showed that 25(OH)D de ciency was more prevalent in CD patients [8,18,25,26,28,33,35,43] .…”
Section: Basic Characteristicsmentioning
confidence: 99%